2015
DOI: 10.1021/acs.energyfuels.5b01099
|View full text |Cite
|
Sign up to set email alerts
|

Low Salinity EOR Effects in Limestone Reservoir Cores Containing Anhydrite: A Discussion of the Chemical Mechanism

Abstract: It is well accepted that seawater injection is able to improve the water wetness of carbonate reservoirs at high temperatures, and in that way, it can act as an enhanced oil recovery (EOR) fluid. A recent laboratory investigation showed that increased oil recovery also was obtained from carbonate reservoir cores by successively flooding composite limestone cores by 2, 10, and 20 times diluted seawater. The study confirmed that it is possible to obtain low salinity EOR effects also in carbonates, and not only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(57 citation statements)
references
References 18 publications
2
55
0
Order By: Relevance
“…One proposed mechanism of improving waterflood performance is to displace asphaltic carboxylates tightly bound to the rock surface by ion complexing and bridging by tailored solution ions (Lager et al 2006(Lager et al , 2007(Lager et al , 2008aStrand et al 2006;Zhang and Austad 2006;Zhang et al 2007b;Sorbie and Collins 2010;Zahid et al 2012;Austad et al 2015;Puntervold et al 2015;Qiao et al 2016). MIE is strongly coupled to rock/brine-surface chemistry.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One proposed mechanism of improving waterflood performance is to displace asphaltic carboxylates tightly bound to the rock surface by ion complexing and bridging by tailored solution ions (Lager et al 2006(Lager et al , 2007(Lager et al , 2008aStrand et al 2006;Zhang and Austad 2006;Zhang et al 2007b;Sorbie and Collins 2010;Zahid et al 2012;Austad et al 2015;Puntervold et al 2015;Qiao et al 2016). MIE is strongly coupled to rock/brine-surface chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, sodium and chloride ions are dominant species at high brine concentrations and may participate in ion-exchange equilibria. It is commonly accepted, however, that sodium and chloride ions are inactive at the calcite/water interface (Somasundaran and Agar 1967;Möller and Werr 1972;Siffert and Fimbel 1984;Thompson and Pownall 1989;Van Cappellen et al 1993;Pokrovsky et al 2000;Nystrom 2001;Wolthers et al 2008;Hiorth et al 2010;Alotaibi et al 2011;Heberling et al 2011;Austad et al 2015;Puntervold et al 2015). Unfortunately, no direct evidence is available to confirm or refute this view.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other laboratory studies and field trials verify the positive effect of low salinity and the importance of brine chemistry on oil recovery. Different studies have shown that for each crude oil/brine/rock (CBR) combination, there are an optimum salinity concentration and certain ion composition that could result in the most optimum incremental oil recovery (Al-Shalabi and Sepehrnoori 2016;Webb et al 2005;Zhang et al 2007;Gupta et al 2011;Honarvar et al 2020;Hiorth et al 2010;Rashid et al 2015;Rezaeidoust et al 2009;Su et al 2019;Strand et al 2003;Austad et al 2015;den Ouden et al 2015;Al-Kharusi et al 2018;Fani et al 2019;Yousef et al 2012;Al-Attar et al 2013;Alameri et al 2014;Ayirala et al 2019;Awolayo et al 2014;Fathi et al 2010;Ghandi et al 2019;Jabbar et al 2013;Jadhunandan and Morrow 1995;Karimi et al 2016;Lashkarbolooki et al 2017;Ligthelm et al 2009;Robertson 2009;Tang and Morrow 1999;Tweheyo et al 2006;Winoto et al 2012;Yousef et al 2010Yousef et al , 2011Yu et al 2008;Zaeri et al 2018;Zahid et al 2012; http://porta l.kaznt u.kz/files /publi cate/2015).…”
Section: Introductionmentioning
confidence: 99%
“…Marius manufactured a new type of high-performance composite using gypsum material and tested its mechanical properties, such as tensile strength [4]. Austa studied the chemical mechanism for low-salinity enhanced oil-recovery effects in carbonates by using a preserved core material containing dissolvable anhydrite [5]. Scholars have also undertaken a large amount of research work that investigates the physical and mechanical properties of anhydrite crystals.…”
mentioning
confidence: 99%